2007
DOI: 10.1177/0886260507305524
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Factors Associated With Sexual Harassment Among Young Female Migrant Workers in Nepal

Abstract: This article explores the extent of, and factors associated with, sexual harassment of young female migrant workers in the carpet and garment factories in Kathmandu Valley. Information is drawn from a survey of 550 female workers aged 14 to 19 and 12 in-depth case histories. Bivariate and multivariate techniques were applied to identify the factors associated with harassment. The survey found that 1 in 10 young women had experienced sexual harassment or coercion. Those who were exposed to pornographic movies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 7 publications
0
22
0
2
Order By: Relevance
“…Alternatively, some women try to develop a greater intimacy with their husbands, communicate sexual desire, and participate more equally in sex-related decision making to avoid unwanted sexual experiences [17-19]. Though a few small-scale studies in Nepal have documented the extent and causes of sexual violence against women within marriage (SVWM), no previous study is known to have focussed on the consequences and coping strategies used by women to avoid SVWM and document the care and support seeking behaviours employed by these women in Nepal [14-16]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, some women try to develop a greater intimacy with their husbands, communicate sexual desire, and participate more equally in sex-related decision making to avoid unwanted sexual experiences [17-19]. Though a few small-scale studies in Nepal have documented the extent and causes of sexual violence against women within marriage (SVWM), no previous study is known to have focussed on the consequences and coping strategies used by women to avoid SVWM and document the care and support seeking behaviours employed by these women in Nepal [14-16]. …”
Section: Introductionmentioning
confidence: 99%
“…These studies found that the prevalence of SVWM ranged from 12% to 50% in Nepal. They also identified various factors, such as women's lack of autonomy, high economic dependency of women on their husbands, men's perceived entitlement to force sex, lack of education and knowledge of sexuality, marriage practices, lack of family and legal support to women, and husband's use of alcohol, that contributed to sexual violence [14-16]. However, very little is known about how women define sexual violence, its negative consequences, and coping mechanisms used to avoid such situations.…”
Section: Introductionmentioning
confidence: 99%
“…Representative studies conducted in the US and Australia revealed that around 20% of women have been sexually coerced [8-10]. Further research conducted among female factory workers in Nepal showed that 1 in 10 had been sexually coerced [11]. Similarly, a non-representative small scale study in Nepal [12,13] found that about half the husbands had forced their wives to have sex.…”
Section: Introductionmentioning
confidence: 99%
“…Health and social issues of internal migrant workers have been highlighted from different parts of the world including China, Bangladesh, Nepal, Thailand, Cambodia, and Mexico (14)(15)(16)(17)(18)(19)(20)(21). High prevalence of nutritional deficiencies such as anaemia, and Vitamin A and D deficiencies were found among female garment factory workers in Dhaka, Bangladesh (14,15).…”
Section: Sri Lanka's First Epz Was Established In 1978 Inmentioning
confidence: 99%
“…High prevalence of nutritional deficiencies such as anaemia, and Vitamin A and D deficiencies were found among female garment factory workers in Dhaka, Bangladesh (14,15). Risky sexual behavior, sexual harassment and violence against women were reported in Nepal and Thailand (17,18,21). Sri Lankan literature indicated that factory workers in EPZ had experienced greater health risks and many adverse health outcomes (22)(23)(24)(25)(26)(27).…”
Section: Sri Lanka's First Epz Was Established In 1978 Inmentioning
confidence: 99%